Genre Analysis and Textual Boundaries to Cultivate Literacy and to Formulate Language English Policy: A Corpus Study of Pisa, TOEFL, English Book and Curriculum - Ficayuma, Lina Aris (ICONELT, 2024)
Genre and text type, primary characteristics of communicative purpose(s), have been implemented in Indonesia since 2006. It has recently gained attention due to the recognition of its pivotal impact on discourse comprehension and production, linguistic realization, and typological text type at global English assessments such as PISA, TOEFL, and IELTS, as well as English curriculum and book development in Indonesia. Hence, this study elucidates the kind of genre category and text types text design in Indonesian English curriculum, English books, TOEFL, and PISA readingassessments to untangle the necessity of the English language learners in Indonesia in preparing them to face TOEFL and PISA tests. Another cultivates their literacy andformulation of English policy—four syntaxes of the interactive Miles and Huberman model adopted for analyzing data. Primary data sources of this qualitative case study research design were collected from curriculum and PISA document analysis, book reviews, and semi-structured interviews. The finding revealed that: a) 7 critical literacy of PISA were identified as determining the purpose of a text, arguing, assessing the relevance/ reliability/ fairness of a source, evaluating the author’s attitude, defining the target audience, and separating fact and opinion; b) school genre priority in Indonesia was not entirely taught and written on PISA text and TOEFL test at their English class, book, and curriculum; it is only 5 of 9 factual genres and 2 of 7 story genres; c) Most of PISA’s classification text type related to the informational typological text whose aims to describe universal text types in terms of the typical surface structure were related to the cognitive process such as judging and consist of attributing sentence, relational concept or elements and phenomenon-linking, spacing phenomenon-registering sentences or action demanding sentence, and aims to achieve a personal purposes. Only a few fictional texts or story genres deal with phenomena in time. It is indicated that genre and text type, integrated into SFL, CA, and GBA, to advance pre-service teachers’ critical literacy, must be comprehensively taught to the genre college level as listed writing skills and key competencies in language for lifelong learning in the 21st century. It implies further research that test takers, policymakers, and teachers who work in English courses, English language policy, and English curriculum need to know the futuristic genre and text types of language learners in the expanding circle country, Indonesia.